INFLUENCE OF PALM OIL BIOMASS CLINKER AND EMPTY FRUIT BUNCH FIBERS ON CONCRETE PROPERTIES - Mohd Haziman Wan Ibrahim; Sajjad Ali Mangi; Sharifah Salwa Mohd Zuki; Ramadhansyah Putra Jaya; Dadang Supriyatno (International Islamic University Malaysia Engineering Journal, 2020)
This study aims to evaluate the influence of palm oil empty fruit bunch (EFB) fibers on flexural strength performance of concrete in the presence of palm oil biomass clinker (POBC). This study considered various proportions of palm oil EFB fibers as 0%, 0.2%, 0.4%, and 0.6% in concrete with fixed amount of POBC as 10%. It was investigated that there is substantial influence of palm oil EFB fibers on properties of concrete containing 10% POBC as sand replacement. The experimental findings of this study indicated that the workability of fresh mix concrete decreases as palm oil EFB fiber content increased. Besides that, hardened properties of concrete were found to be improved as the amount of palm oil EFB fibers increased in the concrete. It was noticed that flexural strength was improved with addition of 0.2% palm oil EFB fibers that act as reinforcement and deliver growth in flexural strength for concrete containing 10% of POBC. Hence, it was concluded that palm oil EFB fiber could be utilized as fiber reinforcement in concrete to improve flexural strength performance of the concrete.